Pengaruh Shariah Compliance dan Spiritual Marketing terhadap Loyalitas Nasabah dengan Kepuasan sebagai Variabel Intervening di Bank Syariah Indonesia Kantor Cabang Palembang Sudirman - Alfira Nurjannah; Heri Junaidi; Chandra Zaki Maulana (Prodi Perbankan Syariah FAI UMT, 2023)
Islamic banks in Indonesia are getting more advanced as indicated by the emergence of Bank Syariah Indonesia which is the result of the merger of three state-owned banks. BSI's success in maintaining customer loyalty is an achievement. The two variables that are suspected of influencing BSI customer loyalty are Shariah Compliance and Spiritual Marketing and are mediated by satisfaction. The research was conducted at BSI KC Palembang Sudirman, because the bank is the largest BSI branch in the city of Palembang. This study aims to determine the direct and indirect effects of the variables used. This research is a quantitative research with 100 customers as respondents and processed using SmartPLS 3. All variables pass the outer model test, then the result of the inner model is that Shariah Compliance does not directly affect customer loyalty and has a negative value. Spiritual Marketing does not affect customer loyalty directly. However, satisfaction can mediate the relationship between the two variables. Shariah Compliance affects customer loyalty mediated by customer satisfaction and Spiritual Marketing affects customer loyalty mediated by customer satisfaction